THE EFFECT OF CONCENTRATION CARRAGEENAN FLOUR AND GLYCEROL AS EDIBLE COATING AGAINST THE CHANGES IN QUALITY OF STROWBERRIES (Fragaria x ananassa) DURING STORAGE - Rita Nopita Sari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Strawberries is one of the horticultural products which have a high economic value however short shelf life. Fruit damaged is mainly caused by  process of respiration and transpiration. One of the manipulation of this factors can be done by coating technique.  The aim of this research was to find out the best coating on strawberries used different concentration of carageenan and glycerol, and observed the changes of physical and chemical on Strawberries during storage. This study used completely randomized design factorial with the first factor of the concentration carrageenan (0.5%, 1%, 1.5%, 2%, 2.5%) and the second factor glycerol concentration (1%, 2%). Data analyzed by analysis of variance (ANOVA) and tested signification by LSD.  The observed parameter during the storage such as hardness, weight loss, soluble solids content, vitamin C and total acid. The result showed with analysis of variance (á=5%)theconcentration of carrageenan significantly on hardness, weight loss, and total acid of Strawberries. The interaction between carrageenan and glycerol concentration significantly on hardness (2ndday) and total acid (4th and 5th day) of strawberries during storage.  The best treatment in this research is combination of carrageenan concentration 2.5% and glycerol concentration 2% (K5G2) able to inhibit decrease of hardness and change of total acid strawberries.Keywords: strawberry, carrageenan, glycerol, edible coating